A brief history of credit in UK higher education : laying siege to the ivory tower - Turnbull, Wayne (Great debates in higher education., 2020)
Although credit is a well-established feature of the higher education sector in the USA, it is a relatively recent and radical phenomenon in the UK. Credit is a vehicle for widening access and student choice, for curricular flexibility and mobility of learning. Credit provides a transparent, enabling framework within which students can be supported and sustained through their learning journey. Yet much of the conservative 'university establishment' in the UK university sector has been hostile to the credit project, hence credit in the UK is both championed and condemned, celebrated and feared, embedded and rejected in different settings. This book provides an introductory overview of credit, chronological chapters which trace the narrative of the history of credit in the UK higher education (decade by decade) from the ground-breaking Robbins Report of 1963 to the present day and a commentary on the developments of the past half-century. Everyone involved, or with an interest, in Higher Education should read this book, including educators (curriculum developers, tutors, assessors) and administrators, institutional leaders and student advisors. Debates about the focus, funding and future of the UK university sector is at the forefront of political and educational discourse; this book could not be more timely. Furthermore, there are no comparable books in the market. This is the first history of credit in the UK HE sector.